2021
DOI: 10.20944/preprints202104.0742.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Emerging role of HDACs: Pathology and Therapeutic targets in Diabetes Mellitus

Abstract: Diabetes mellitus (DM) is one of the principal manifestations of metabolic syndrome and its prevalence with modern lifestyle is increasing incessantly. Chronic hyperglycemia can induce several vascular complications that were referred to be the major cause of morbidity and mortality in DM. Although several therapeutic targets have been identified and accessed clinically, the imminent risk of DM and its prevalence are still ascending. Substantial pieces of evidence revealed that histone deacetylase (HDAC) isofo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 271 publications
(458 reference statements)
0
4
0
Order By: Relevance
“…DCM has been a concern by scholars since it was proposed in 1972, but the related research on DCM did not show explosive growth until 2004 (3,7). Researchers have studied the pathogenesis of DCM from different perspectives, such as impaired myocardial insulin signaling, mitochondrial dysfunction, endoplasmic reticulum (ER) stress, impaired calcium homeostasis, abnormal coronary microcirculation, activation of the sympathetic nervous system (SNS), activation of the renin-angiotensin-aldosterone system (RAAS), and maladaptive immune responses (8)(9)(10)(11)(12)(13)(14)(15). There is a lack of accurate diagnostic criteria for DCM.…”
Section: Introductionmentioning
confidence: 99%
“…DCM has been a concern by scholars since it was proposed in 1972, but the related research on DCM did not show explosive growth until 2004 (3,7). Researchers have studied the pathogenesis of DCM from different perspectives, such as impaired myocardial insulin signaling, mitochondrial dysfunction, endoplasmic reticulum (ER) stress, impaired calcium homeostasis, abnormal coronary microcirculation, activation of the sympathetic nervous system (SNS), activation of the renin-angiotensin-aldosterone system (RAAS), and maladaptive immune responses (8)(9)(10)(11)(12)(13)(14)(15). There is a lack of accurate diagnostic criteria for DCM.…”
Section: Introductionmentioning
confidence: 99%
“…Although autophagy is important for maintaining cellular homeostasis in healthy cardiac tissues by preventing the accumulation of dysfunctional organelles and cytotoxic protein aggregates, some recent research has found that this process is frequently impaired in diabetic hearts (91). There are contradictory evidences regarding whether autophagy flux is upregulated or downregulated in the hearts of DM patients.…”
Section: Role Of Autophagy In Diabetic Hfmentioning
confidence: 99%
“…Appropriate programmed cell death such as apoptosis and autophagy seems to be an essential part in the elimination of cytotoxic proteins and dysfunctional organelles which would otherwise accelerate the development of DCM and the deterioration of DCM to cardiac failure. And, more and more evidences revealed that suppression of excessive cardiomyocyte death of aforementioned death modes occurred in the diabetic heart may yield tremendous advantageous effects on DCM (126)(127)(128). It is well known that FoxO1 and/or FoxO3a participate in the regulation of various cell death seen during insulin resistance and diabetes.…”
Section: Cardiomyocyte Apoptosis and Autophagymentioning
confidence: 99%
“…With apoptosis, FoxO transcription factors are downstream targets of the Akt kinase which regulates processes of cellular proliferation and survival and also may indirectly stimulate expression of death receptor ligands such as Fas ligand through the unstable mitochondrial channels or directly induce the expression of multiple pro-apoptotic proteins like Bcl-2 family (18,25,129). As for autophagy, researchers have shown that plenty of the regulation and control mechanisms include but are not limited to the mTOR/AMPK, FoxOs, SIRTs, and others signalings, and further studies to unmask the detailed roles and in particular the potentially complicated interplays of the pathways should help to elucidate the inconsistent outcomes observed following the intervention of the individual pathways in the treatment of DCM (127,130). Convincing evidences showed that certain drugs protected pancreatic β-cells by enhancing autophagy such as liraglutide (a long-acting human glucagonlike peptide-1 analog), which protected insulinoma cells via alleviating apoptosis accompanied by a significant increase of autophagy under hyperglycemia in vitro (131).…”
Section: Cardiomyocyte Apoptosis and Autophagymentioning
confidence: 99%